2024
DOI: 10.1002/wer.11026
|View full text |Cite
|
Sign up to set email alerts
|

Wastewater treatment using moving bed biofilm reactor technology: a case study of ceramic industry

Atharv Pethe,
Mousumi Debnath

Abstract: Biological approaches and coagulation are frequently used to reduce the chemical oxygen demand (COD) for treatment of ceramic effluent water. The technology known as the moving bed biofilm reactor (MBBR) can accomplish this goal. Further, the process of emulsification‐aided innovative MBBR using biosurfactants can be proposed for ceramic effluent treatment. In a step‐by‐step upgrading scheme, biosurfactants and a consortia of halophilic and halotolerant microbial culture was utilized for the treatment of the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 32 publications
0
0
0
Order By: Relevance
“…25 In a recent case study, a mixture of halophilic biosurfactants extracted from a consortium of bacteria along with the consortia of bacteria was used for the treatment of ceramic wastewater on a lab scale, pilot scale, and industry scale, where great reduction was observed in BOD, COD, TSS, total dissolved solids (TDSs), and heavy metals. 26 Microorganisms also assist in the bioremediation of heavy metals, because they may interact with metals through a variety of ways that allow them to tolerate their toxicity. Using contamination as a source of nourishment and defending organisms from toxic effects are the two major strategies by which the organisms can deal with pollutants.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…25 In a recent case study, a mixture of halophilic biosurfactants extracted from a consortium of bacteria along with the consortia of bacteria was used for the treatment of ceramic wastewater on a lab scale, pilot scale, and industry scale, where great reduction was observed in BOD, COD, TSS, total dissolved solids (TDSs), and heavy metals. 26 Microorganisms also assist in the bioremediation of heavy metals, because they may interact with metals through a variety of ways that allow them to tolerate their toxicity. Using contamination as a source of nourishment and defending organisms from toxic effects are the two major strategies by which the organisms can deal with pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most crucial ways that an organism can protect itself from the harmful effects of heavy metals is through a flux system, a kind of extracellular sequestration, which forms an outer layer of defense and expels the metal ions from the cytoplasm into the periplasmic region. 26 However, the independent metabolism includes intracellular sequestering (bioaccumulation) and biotransformation. In a recent study, it was reported that the ABC transporters and natural resistance-associated macrophage protein (NRAMP) transporters mediate the uptake of specific metal ions in the cytosol of bacterial cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation